MENGGAPAI SAKINAH, MAWADDAH, DAN RAHMAH DALAM PERNIKAHAN PERSPEKTIF MARXISME DAN SUFISME - Ach Faisol (Fakultas Agama Islam UNISMA, 2021)
This article seeks to answer the question of how a married couple can achieve sakinah, mawaddah, and rahmah families. To get the answer, the writer conducted a qualitative research by tracing written sources historically-chronologically-philosophically with a concentration on Marxism and Sufism. Although the author is also a taker of several other figures. The author gets the answer that a husband and wife partner to be able to reach a sakinah, mawaddah, and rahmah family must take a winding road and a long process. If a married couple has succeeded in achieving it, then that is a happy family. The ideal happy family according to the Quran is to have succeeded in achieving a solid degree of faith in Allah SWT and knowledgeable.Keywords: Sakinah, mawaddah, and rahmah, Marxism, Sufism